Prayers of a stranger ebook A christmas story. - Bunn, Davis (2012)
While visiting the Holy Land, Amanda answers the prayers of a stranger . . . and begins an amazing Christmas journey. Amanda Vance is ambivalent about her husband's idea for a big family holiday up north. Last year she planned a special Christmas in their own home, carefully preparing a nursery and the keepsake ornaments for their newborn. Now that room stands as empty as her heart. Then a neighbor's mishap turns into a last-minute chance for Amanda to take a much-needed vacation to tour the Holy Land. An extraordinary turn of events allows Amanda to help answer a young mother's plea for healing. Then, filled with a sense of awe, Amanda visits the place of Jesus' birth. There she discovers anew the miracle of the Christ child—God incarnate as a tiny, vulnerable baby. Her return to Florida marks a momentous shift in her soul and in her marriage as she begins to realize that her journey didn't end in the Holy Land. And that God doesn't just answer prayers of strangers . . . but also those of her own heart. "A great story filled with emotion, depth, and spiritual beauty." —Debbie Macomber, #1 New York Times Best-selling Author